Implementation of Cash for Work Program for Post Disaster Emergency Recovery Process Based on Experience in Post War Resettlement Process through Emergency Northern Recovery Project of Sri Lankan RJSSM - Sivakumar, S.; Janen, S. (The International Journal Research Publications, 2014)
Immediately after the resettlement process of post war resettlement in Sri Lanka, Livelihoods of the IDPs were critically poor and Cash for Work (CfW) is the element facilitates the community for their short term employment; it also creates a community ownership through the direct participation of community in the reconstruction of their own village. This facilitated the community strengthening with livelihood development. This study area confines in Northern Provence of Sri Lanka. Continuous review was carried out since the begging of the CfW programme up to the final stage of CfW programme. Focus Group Discussion (FGD) and Impact assessment survey was carried out to find out the strength, weakness of implementation and visualize the livelihood development. Monitoring and Evaluation process facilitated to modification of the programme. Finally, Generalized Model for Implementation of CfW for post emergency situation was developed. The common recommendation for CfW were; carrying out baseline data collection, developing overall objective, setting target for CfW program, determine the wage rate for CfW program, recruitment and motivation of staffs, decide whether to collaborate with local NGOs, select community based existing committee or new CfW committee, strengthening the community groups, baseline profile of beneficiaries, selection of subproject, design & implement the selected project, chose a reliable method for payment, set up monitoring & evaluation system and develop a phasing out strategy to meet the sustainability of the CfW programme. By implementing the proposed structure of CfW program will help to uplift the community’s socio economic status with sustainable manner in the future CfW programme.
Keywords: Resource - Community